2005
DOI: 10.1093/humrep/dei401
|View full text |Cite
|
Sign up to set email alerts
|

Study of two markers of apoptosis and meiotic segregation in ejaculated sperm of chromosomal translocation carrier patients

Abstract: Our data show a predominant proportion of balanced gametes in sperm of chromosomal translocation carrier patients. Moreover, PS externalization and DNA fragmentation rates are significantly higher in ejaculated sperm of these patients than in donor sperm. These tests could be used to predict the outcome of ICSI for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 50 publications
8
52
1
5
Order By: Relevance
“…Negative correlation has been associated between fertilization results with the presence of high levels of sperm DNA fragmentation [9,[36][37][38][39]. However, if the type and extent of DNA damage can be balanced by the reparative ability of the oocyte, it is possible to achieve fertilization even in the presence of elevated sperm DNA fragmentation rates [10,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Negative correlation has been associated between fertilization results with the presence of high levels of sperm DNA fragmentation [9,[36][37][38][39]. However, if the type and extent of DNA damage can be balanced by the reparative ability of the oocyte, it is possible to achieve fertilization even in the presence of elevated sperm DNA fragmentation rates [10,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sperm apoptosis, Brugnon et al [18] found phosphatidylserine externalization, a typical marker of apoptosis, and significantly higher DNA frag mentation rates in ejaculated spermatozoa from translo cation carriers than in spermatozoa from donors.…”
Section: Discussionmentioning
confidence: 99%
“…It can be argued that this association between chromosomal imbalance and DNA fragmentation has only been shown in ten patients so far (four by Perrin et al in [18], and six in the present study). However, since the association between DNA fragmentation, apoptosis markers, and chromosomal rearrangements has been evidenced in multiple studies [6,7,17], it is possible than in most if not all of the patients analyzed in those studies, DNA fragmentation is more often found among unbalanced spermatozoa. Therefore, it is likely that our population of six patients is representative of the chromosomal events in sperm from translocations carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the subject stated that chromosomal rearrangements were associated with elevated global levels of DNA fragmentation and apoptosis [6,7,17]. However those studies were carried out in reproductive medicine centers, and most subjects initially consulted for infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation